Modeling of a micro-diaphragm biosensor for human artery pulse wave detection - Hasikin, K.; Ibrahim, F.; Soin, N. (2008)
The analysis of the behavior of the micro-diaphragm biosensor for human artery pulse wave detection has been presented in this paper. This includes the study of the effect of the diaphragm structural parameters on the static and dynamic performances such as sensitivity and natural frequency. It can be concluded that the modeled micro-diaphragm with a radius of 175pm and thickness of 4pm respectively has satisfied the maximum allowable deflection and operates in optimum frequency response. Â©2008 IEEE.